2020
DOI: 10.1007/s13353-020-00554-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gene therapy for canine monogenic diseases on the progress of preclinical studies

Abstract: Rapid progress in knowledge of the organization of the dog genome has facilitated the identification of the mutations responsible for numerous monogenic diseases, which usually present a breed-specific distribution. The majority of these diseases have clinical and molecular counterparts in humans. The affected dogs have thus become valuable models for preclinical studies of gene therapy for problems such as eye diseases, immunodeficiency, lysosomal storage diseases, hemophilia, and muscular dystrophy. Successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Numerous animal models of different genetic subtypes of IRDs replicated the human phenotypes enough to develop and test novel therapies to improve outcomes for IRD patients. 1,2 The first gene replacement therapy indicated for IRD, Luxturna (voretigene neparvovec-rzyl), was approved by Health Canada in October 2020 and is now available to patients with vision loss due to inherited retinal dystrophy caused by confirmed biallelic RPE65 mutations. Clinicians from Ontario, Quebec and Alberta can now access this treatment through their province's public health plan.…”
Section: A B O U T T H E a U T H O R Smentioning
confidence: 99%
“…Numerous animal models of different genetic subtypes of IRDs replicated the human phenotypes enough to develop and test novel therapies to improve outcomes for IRD patients. 1,2 The first gene replacement therapy indicated for IRD, Luxturna (voretigene neparvovec-rzyl), was approved by Health Canada in October 2020 and is now available to patients with vision loss due to inherited retinal dystrophy caused by confirmed biallelic RPE65 mutations. Clinicians from Ontario, Quebec and Alberta can now access this treatment through their province's public health plan.…”
Section: A B O U T T H E a U T H O R Smentioning
confidence: 99%
“…The domestic dog has also been recognized as a valuable model of monogenic diseases in humans and possesses key advantages over inbred rodent models classically used for preclinical studies regarding gene therapy. Not only do causative mutations spontaneously occur in dogs as they do in humans, detailed pedigrees and opportunities to evaluate treatments over a long-term, often years, provide crucial advantages in a preclinical setting (Switonski, 2020).…”
Section: Revitalizing Cells Tissues and Organs In Vivomentioning
confidence: 99%
“…As of 2017, hundreds of gene therapy trials have been undertaken to deal with monogenic diseases and researchers have recently been able to shed light on the molecular mechanisms underpinning many disorders to pave the way for novel interventions utilizing gene therapy. Beginning in 1993, the First International DogMap Meeting in Oslo, Norway sought to gain a more in-depth understanding of the genetics driving approximately 700 monogenic diseases known to afflict dog breeds (Switonski, 2020). Although analysis of genome sequence variations between different dog breeds is currently underway (Ostrander et al, 2019), known causative mutations are continuously being identified and approximately 430 monogenic diseases in dogs have the potential to serve as preclinical models for homologous human diseases (Switonski, 2020).…”
Section: Revitalizing Cells Tissues and Organs In Vivomentioning
confidence: 99%
See 2 more Smart Citations